Análise genética da aleurona incolor em raças mexicanas de milho - Taborda Romero, Felix (1955)
The present paper is concerned with the genetic of uncolored aleurone of mexican races of maize. Initially the plants of the mexican races were crossed with the plants of Negrito - one ancient race of maize, with colored aleurone, from Colombia. Inbreeding the F1 plants was obtained the segregating F2 ears. A statistical analysis was elaborated for the observed segregations in 523 F2 ears with 203963 grains, by means of X2 test. An analysis of 391 F3 ears, proceeding of F3 plants derivated of white grains from F2 ears confirmed the observed segregations. The observed results agreed with a hypothesis about the effect of recessive gene dosage in heterozygotes. The effect of recessive gene dosage result in an increment of the frequency of fenotypes with the recessive character. This effect was referred for the explanation of some apparent irregularities of mendelian ratios. Graphics are presented to illustrate the effect of recessive gene dosage. One hundred nineteen crosses were performed with genetics testers of constitution cc and rr. The results of these testers-crosses demonstrate that r is the common gene inhibitor of the mexican races studied, being its frequency of about 80%; aleles Cc having a randomized distribution of about 50%. Both these genes frequencies are in according with Hardy-Weinberg law. The conclusions after studying the observed results in F2 and F3 ears are the following: 1º) The uncolored aleurone in the race Harinoso de Ocho, Tuxpeño, sub-race Elotes occidentales, and in Coahuila, Carmen, and Capiten (samples of the races Tuxpeño) is condicionated to the effects of one, two and three recessive inhibitors. 2º) The uncolored aleurone in the races Chapalote, Reventador, Vandeño and Cuba Amarillo is avoid to the effects of two and three recessive inhibitors. 3º) The uncolored aleurone in the race Celaya is avoid to the effects of one two and three recessives inhibitors and to the effects of the dominant inhibitor alele cI. 4º) The uncolored aleurone in the races Tabloncillo, Tehua, Tepecintle, Zapalote Grande, sub-race Perla and in Guanajuato 61 (sample of Celaya), is avoid to the effects of one, two, and three recessive inhibitors and to the effects of the dominant inhibitor alele cI.